Drought Stress Effects on Triticum spelta L. Structural and Functional Characteristics - Kosakivska I.V.; Vasyuk V.A.; Babenko L.M.; Voytenko L.V. (Journal of Stress Physiology & Biochemistry, 2018)
Effects of a soil drought on the growth, microstructure of leaf surface and photosynthetic pigments composition of Triticum spelta L. 14-days-old plants have been studied. It was shown that the root system whose length diminished by 19% and weight - by 48% turned out to be more sensitive to the impact of a 4-day soil drought. On the 23d day after rehabilitation the difference between biometric parameters of control and experiment samples reduced, but a complete recovery of plants did not occur. A microstructural analysis of the amphistomatic leaf lamina revealed the same number of stomata with similar sizes of stomatal pores on the adaxial and abaxial surface. Following the soil drought, some increase in wax density was observed, stomata on the both leaf surfaces remained closed. The pigment complex of 14-days-old plants responded by decreasing the quantity of chlorophyll and carotenoids. On the 23th day after rehabilitation a further decrease in the photosynthetic pigments level was observed. The changes in the ratio of pigments content after stress and peculiarities of microstructure of leaf surface corresponded with drought tolerance of T. spelta. The retention of rather high parameters of the green pigment content immediately after dehydration on the 18th day corresponded to biometric study data demonstrating a stable growth in the plant over ground part.